Prospective, Observational Study of the Clinical Outcomes of FVIII Treatment in Adults and Adolescents with Severe Haemophilia A - Chowdary, Pratima; Khoo, Liane; Wang, Michael; Chambost, Hervé; Chan, Anthony K.C.; Willemze, Annemieke; Oldenburg, Johannes (TH Open, 2025)
To assess real-world treatment patterns and outcomes in previously treated patients ≥12 years old with severe haemophilia A treated with marketed factor VIII (FVIII) replacement products.Data were collected prospectively between 25 January 2019 and 30 November 2020 across 45 sites in 17 countries. Primary endpoint was annualized bleed rate (ABR). Secondary endpoints included factor consumption, bleed treatment, joint health, and safety. Exploratory endpoints included pain and quality of life outcomes.A total of 157 patients received ≥1 FVIII injection (prophylaxis n = 139, on-demand n = 19). Mean (standard deviation; SD) observation period was 43.1 (13.3) weeks. Median (quarter [Q]1, Q3) ABR was 2.0 (0.0, 5.7) for those on prophylaxis. Those receiving standard half-life FVIII products or extended half-life FVIII products had a median (IQR) ABR of 2.2 (0.0, 6.1) and 1.3 (0.0, 5.0), respectively. Still, only 35% of patients on prophylaxis experienced zero bleeds and 18% had more than five bleeds in a year. Approximately 23% of bleeding episodes required >1 FVIII dose for resolution. The mean (SD) number of routine prophylaxis injections/week was 2.2 (1.1). Median (Q1, Q3) annualized factor consumption for patients on prophylaxis was 4,106.4 (3,151.6, 5,291.2) IU/kg/year. No changes in Haemophilia Joint Health Score (mean [SD] of 16.1 [19.3] versus 15.7 [17.7]), PROMIS pain intensity 3a T-score (mean [SD] 41.6 [8.2] versus 40.9 [9.1]), or Haem-A-QoL (mean [SD] 30.6 [17.3] versus 29.5 [17.4]) were observed between baseline and the end of the observation period for those using prophylaxis.Prophylaxis using standard or extended half-life FVIII replacement therapies achieves adequate haemostatic control in only about half of patients, with some experiencing very poor outcomes. Real-world data highlight the urgent need to optimize prophylaxis to enhance haemostatic control, ideally achieving a zero ABR and its associated benefits.
Keywords: observational study; clinical study; haemophilia a; factor VIII; prospective studies